2012
DOI: 10.1097/aap.0b013e3182576b6f
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Comparison Between Perivascular and Perineural Ultrasound-Guided Axillary Brachial Plexus Block

Abstract: Perivascular and PN ultrasound-guided AXBs result in comparable success rates and total anesthesia-related times. Because of fewer needle passes and a shorter performance time, the PV technique provides a simple alternative for ultrasound-guided AXB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 10 publications
4
99
1
5
Order By: Relevance
“…The execution time is not affected by the method used to perform the block, the values obtained in this respect for the two groups of patients being very close and with no significant difference. Moreover, the literature shows similar results; a study conducted in 2012 obtained similar results when using the ultrasound method for axillary brachial plexus block -12.2 minutes [8] and another study, again in 2012, presented a performing time of 15.7 minutes [9].…”
Section: Discussionsupporting
confidence: 64%
“…The execution time is not affected by the method used to perform the block, the values obtained in this respect for the two groups of patients being very close and with no significant difference. Moreover, the literature shows similar results; a study conducted in 2012 obtained similar results when using the ultrasound method for axillary brachial plexus block -12.2 minutes [8] and another study, again in 2012, presented a performing time of 15.7 minutes [9].…”
Section: Discussionsupporting
confidence: 64%
“…Two recent studies have shown that two injections (one around the musculocutaneous nerve and another posterior to the axillary artery) provide an equivalent success rate than the identification and injection of each of the four major nerves. 30,31 In addition to reducing the time needed to perform the block, this technique requires the operator to identify only the musculocutaneous nerve, which greatly simplifies the technique (Fig. 9) (Videos 4a and 4b, available as ESM).…”
Section: Axillary Approachmentioning
confidence: 99%
“…Deux études récentes ont démontré que deux injections (une autour du nerf musculocutané et une seconde en postérieur de l'artère axillaire) procurent un aussi bon taux de succès que l'identification et l'injection de chacun des quatre nerfs majeurs. 30,31 En plus de réduire la durée de réalisation du bloc, cette technique nécessite uniquement l'identification du nerf musculocutané, simplifiant grandement la technique (Fig. 9), (Vidéos 4a et 4b, disponibles en matériel électronique supplémentaire).…”
Section: Approche Infraclaviculaireunclassified
“…23 The AXB was performed according to a previously described technique. [24][25][26] All patients received 1.0% lidocaine-0.25% bupivacaine (obtained by mixing equal parts of 2% lidocaine and 0.5% bupivacaine) with epinephrine 5 lgÁmL -1 . A SonoSite M-Turbo TM US machine (SonoSite Inc, Bothell, WA, USA) and a 6-13 MHz linear US probe were used in all subjects.…”
Section: Résumémentioning
confidence: 99%